CDK1 Regulates Mediator of DNA Damage Checkpoint 1 (MDC1) During Mitotic DNA Damage - Yu, Bing (2012)
Cells engage sophisticated programs of DNA damage response (DDR) and repair to guard against genetic mutations. While there is significant knowledge concerning DDR in interphase cells, much less is known about these processes in mitosis. Direct interaction between MDC1, a master DDR organizer, and a marker of DNA damage, histone γH2AX, is required to trigger robust repair. Here we show that the DNA damage-induced interaction between MDC1 and γH2AX is attenuated in mitosis. Furthermore, inhibition in the activity of the core mitotic regulator CDK1, either by pharmacological inhibition or siRNA attenuation, enhances MDC1-γH2AX colocalization in mitosis. Our findings offer key new insights into how DDR is controlled during mitosis.